ITT brands team up to serve Mexican offshore energy market. Issue 10 (October 2015) - Unknown
Abstract : ITT Corp's C'treat and Bombas Goulds de Mexico (BGM) brands have formed an alliance to deliver large-scale seawater, potable water and high-purity water solutions to the offshore energy industry in Mexico.